Energy Performance of Fuzzy Logic Controllers in Smart Buildings - Baniyounes, Ali; Ghadi, Yazeed; Abu Baker, Ayman (International Journal of Energy Economics and Policy, 2018)
This article presents simulation study on using fuzzy logic based controllers in order to determine building's occupancy level and hence its effect on energy usage. The projected results of energy savings then is used to determine and investigate the proposed fuzzy logic based control system environmental and economic aspects. The proposed system energy performance are measured based on the system occupancy density level, Daylight utilization and natural ambient air and humidity. The simulation and modelling engines used in this article are MATLAB and EnergyPlus. Results showed that system will save 14% of total energy demand at 50 % of occupancy level compared to total energy demand at full occupancy level (100% occupancy level) and also it is able to save 24% of total energy demand at 25 % of occupancy level compared to full occupancy level energy demand (100% occupancy level). Keywords: Daylight, Occupancy level, Fuzzy logic JEL Classifications: K32, O13 DOI: https://doi.org/10.32479/ijeep.6393